THE EFFECTS DISPOSITIONAL AND SITUATIONAL COGNITIVE FACTORS ON THE INTENTION TO USE INTERNET: AN EMPIRICAL STUDY OF THE ACCEPTANCE OF INFORMATION TECHNOLOGY AT UNIVERSITAS BENGKULU - Abdillah, Willy (Journal of Indonesian Economy and Business, 2009)
The objective of this research is to investigate the effect of dispositional personality and situational cognitive factors on the intention to use the internet. Personality factors were measured by five variables openness to experience, conscientiousness, extraversion, agreeableness and neuroticism. Meanwhile, situational cognitive factors were measured by perceived ease of use, perceived usefulness and self-efficacy. Survey was conducted to 323 students of Faculty of Economics, Universitas Bengkulu, include extension and Magister Management students programme. This research uses non-probability sampling procedure with purposive-judgment method. Primary data were gathered using closedquestion form questionnaire. Hypotheses testing were conducted using Partial Least Square with software SmartPLS version 2.0.M3. Results showed that openness to experience, perceived usefulness and self-efficacy significantly affect intention to useÂ internet. Meanwhile, situational cognitive factors were better predictor than personality factors on the intention to use internet. This suggests that the application of information technology acceptance and adoption theory dominantly based on perceptual cognitive factors rather than personality. The current study contributes to higher education managers in terms of how to manage common problems of information system resistance.Keywords: dispositional personality, situational cognitive, Information TechnologyÂ Acceptance, and Information System.